Shelf life Extension of Tuna Fillets by Gelatin and Chitosan Based Edible Coating Incorporated with Clove Oil - Kumar, K. Sathish; Chrisolite, B.; Sugumar, G.; Bindu, J.; Venkateshwarlu, G. (Fishery Technology, 2018)
The present study aimed to develop bioactive ediblecoating (BEC) solutions from gelatin and chitosan,incorporated with different concentrations of cloveoil as a natural preservative and evaluate their effecton shelf life of tuna fillets. The antibacterial activityagainst 11 fish spoilage and fish-borne bacteria weretested by agar well diffusion method, minimuminhibitory concentration (MIC) and minimum bactericidalconcentration (MBC). Gram positive bacteriawere more susceptible than gram negativebacteria. Among all the tested bacteria, Bacilluscereus and Staphylococcus aureus were most sensitiveto BEC solutions. The tuna fillets were dipped inBEC solutions with different concentrations viz., 1%Acetic acid, 1% Chitosan (C), 1% Gelatin + 1% Cloveoil (GC), 1% Chitosan + 1% Clove oil (CC), 1%Gelatin + 1% Chitosan + 1% Clove oil (GCC) andchanges in APC, TBARS, TVB-N and sensory valueswere studied during storage under refrigeratedcondition (4Â°C). The fillets without dip treatmentwas considered as control. Dip treatment of BECsolutions significantly delayed the rate of microbialspoilage and extended the shelf life of tuna filletsby six days during refrigerated storage. Solutionsincorporated with clove oil, especially fillets treatedwith 1% gelatin + 1% chitosan + 1% clove oil (GCC)solution had better in-vitro antimicrobial propertiesand showed excellent preservative action on tunafillets. The BEC solutions incorporated with cloveoil demonstrated its potential as an excellent naturalantibacterial agent which can be used as an effectivealternative to synthetic antibacterial agents and could be used for packaging of tuna and other fishery products.